Epidemiology of pregnant patients with major trauma in Victoria. (23rd June 2021) - Sato, Nobuhiro; Cameron, Peter; Thomson, Benjamin NJ; Read, David; McLellan, Susan; Woodward, Anthony; Beck, Ben
Abstract: Objective: Trauma is one of the most common contributors to maternal and foetal morbidity and mortality. The aim of the present study was to describe the characteristics and outcomes of major trauma in pregnant patients using a population‐based registry. Methods: Registry‐based study using data from the Victorian State Trauma Registry (VSTR), a population‐based database of all hospitalised major trauma (death due to injury, Injury Severity Score [ISS] ≥12, admission to an intensive care unit [ICU] for more than 24 h and requiring mechanical ventilation for at least part of their ICU stay or urgent surgery) in Victoria, Australia, from 1 July 2007 to 30 June 2019. Pregnant patients with major trauma were identified on the VSTR. We summarised patient data using descriptive statistics. Results: Over the 12‐year study period, there were 63 pregnant major trauma patients. Fifty‐two (82.5%) patients sustained injuries resulting from road transport collisions. The maternal survival rate was 98.4% and the foetal survival rate was 88.9%. Thoracic injury was the most common injury (25/63), followed by abdominal injury (23/63). Eighty‐six percent of the third trimester patients (19/22) were transported directly to a major trauma service with capacity for definitive care of the pregnancy. Conclusion: The present study demonstrated road transport injury was the most common mechanism of injury and both maternal survival rates and foetal survival rates were high. This information is essential for trauma care system planning and public health initiatives to improve the clinical management and outcomes of pregnant women with major trauma. Abstract : Our study showed very low numbers of presentations of pregnant patients with major trauma using a population‐based registry. Both maternal survival rates and foetal survival rates were high. The majority of third trimester pregnant women were triaged to the appropriate Trauma centre.